2015
DOI: 10.3329/nimcj.v6i1.23158
|View full text |Cite
|
Sign up to set email alerts
|

Practice of personal hygiene among rural women of a selected community in Bangladesh

Abstract: Background : Good health is a marker of good economic status of a nation. Personal hygiene should be maintained first for obtaining great accuracy in work, low suffering from diseases and to reduce possibility of diseases. Objective : This study was undertaken to assess practice of personal hygiene among rural women of a selected community in Bangladesh. Materials & Methods : A descriptive type of cross sectional study was conducted during March-June 2012. 150 women of various ages selected from Garibpur and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
1
4
0
2
Order By: Relevance
“…Most of the women of Northern Bangladesh know that they need to wash hand before eating food. Similar result was also found in a study conducted at Jessore district of Bangladesh [24]. A significant difference (χ 2 = 10.86, P˂0.01) was found among the mother of three district of Northern Bangladesh in the habit of washing hand before feeding child.…”
Section: Regional Variation In Hygiene Practice Among the Womensupporting
confidence: 86%
See 2 more Smart Citations
“…Most of the women of Northern Bangladesh know that they need to wash hand before eating food. Similar result was also found in a study conducted at Jessore district of Bangladesh [24]. A significant difference (χ 2 = 10.86, P˂0.01) was found among the mother of three district of Northern Bangladesh in the habit of washing hand before feeding child.…”
Section: Regional Variation In Hygiene Practice Among the Womensupporting
confidence: 86%
“…But it is sorry to share that 80% of the fisherman used water only for washing hand. Sometimes it is found that people are over concern on washing hand before eating regular meals but remain halfhearted to wash hand before eating any dry foods [24]. Similarly Sinha et al [25] found that 95% of the women washed their hands after using toilet but only 35% of them washed their hand before and after their meal.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Each year, over 5 million children in developing countries die from either diarrhea or acute respiratory infections [11].Globally handwashing with soap at key times is as low as 2 to 35% [12]. An average of 65% of death caused by diarrheal diseases could be reduced if good hygiene practice accompanies with the provision of water and sanitation [13].…”
Section: Introductionmentioning
confidence: 99%
“…Учеными и международными организациями, включая ВОЗ, ЮНИСЕФ и др., отмечается взаимосвязь состояния здоровья с обеспечением санитарии и гигиены; предложены руководящие принципы в области обеспечения безопасного сбора, хранения и удаления нечистот с акцентом на принятие мер, направленных на противодействие распространению короновирусной инфекции и учетом экономических факторов домохозяйств [16,20,22,63,105,120,128,143,146,147]. Доказано, что распространенность инфекционных заболеваний зависит от уровня соблюдения гигиены рук, личной гигиены, соблюдения правил обращения с пищевыми продуктами [2,10,17,22,31,42,70,75,98,105,114,124,133,142,146].…”
Section: Introductionunclassified